Helio Gallardo: between impossible and necesarry Marxism - García Quesada , George (2023)
This essay explores the conception of Marxism in Helio Gallardo’s work. It discusses what we consider a constitutive tension in this concept: that between the impossibility to establish a single and definitive Marxism, and the need for Marxism as a theory for human emancipation.